Overall survival for neuroblastoma in South Africa between 2000 and 2014. Issue 11 (31st July 2019) - Van Heerden, Jaques; Hendricks, Marc; Geel, Jennifer; Sartorius, Benn; Hadley, G. P.; Du Plessis, Jan; Büchner, Ané; Naidu, Gita; Van Emmenes, Barry; Van Zyl, Anel; Kruger, Mariana
Abstract: Background: Outcome data for neuroblastoma in sub‐Saharan Africa are minimal, whereas poor outcome is reported in low‐ and middle‐income countries. A multi‐institutional retrospective study across South Africa was undertaken to determine outcome. Methods: Patients treated between January 2000 and December 2014 in nine South African pediatric oncology units were included. Kaplan–Meier curves and Cox regression models were employed to determine two‐year survival rates and to identify prognostic factors. Results: Data from 390 patients were analyzed. The median age was 39.9 months (range, 0–201 months). The majority presented with stage 4 disease (70%). The main chemotherapy regimens were OPEC/OJEC (44.8%), St Jude NB84 protocol (28.96%), and Rapid COJEC (22.17%). Only 44.4% had surgery across all risk groups, whereas only 16.5% of high‐risk patients received radiotherapy. The two‐year overall survival (OS) for the whole cohort was 37.6%: 94.1%, 81.6%, and 66.7%, respectively, for the very‐low‐risk, low‐risk, and intermediate‐risk groups and 27.6% for the high‐risk group ( P < 0.001, 95% CI). The median survival time for the whole group was 13 months (mean, 41.9 months; range, 0.1–209 months). MYCN‐nonamplified patients had a superior two‐year OS of 51.3% in comparison with MYCN‐amplified patients at 37.3% ( P = 0.002, 95% CI). Conclusions: Limited disease had an OS comparable with high‐income countries, but advanced disease had a poor OS. South Africa should focus on early diagnosis and implementation of a national protocol with equitable access to treatment.